Researcb on tbe Arcbitecture of Reconfigurable Fundamental Information Communication Network - Julong Lan; Gang Xiong; Yuxiang Hu; Shiran Liu; Dongnian Cheng (Dianxin kexue)
With the enlargement of network scale and deployment of various new business,it is becoming more and more obvious that the statical and rigid architecture of the IP network is deficient in business adaptability,transport ability,security and controllability and so on.This fact makes the clean-slate design of future internet architecture be a hot research topic.Against this background,new ideas and methods for the internet development based on the advantage of reconfigurable technology with flexibility,scalability and adaptability were provided.The practice shows that the research results of the project have given solutions for some fundamental problems of network,and produced important influences on related fields at home and abroad.